Kinetic and stoichiometric characterization of a fixed biofilm reactor by pulse respirometry - Ordaz, Alberto (2012)
An in situ respirometric technique was applied to a sequential biofilm batch reactor treating a synthetic wastewater containing acetate. In this reactor, inoculated with mixed liquor from a wastewater plant, unglazed ceramic tiles were used as support media while maintaining complete mixing regime. A total of 8 kinetic and stoichiometric parameters were determined by pulse respirometry, namely substrate oxidation yield, biomass growth yield, storage yield, storage growth yield, substrate affinity constant, storage affinity constant, storage kinetic constant and maximum oxygen uptake rate. Additionally, biofilm growth was determined from support media sampling showing that the colonization process occurred during the first 40 days, reaching an apparent steady-state afterward. Similarly, most of the stoichiometric and kinetic parameters were changing over time but reached steady values after day 40. During the experiment, the respirometric method allowed to quantify the amount of substrate directed to storage, which was significant, especially at substrate concentration superior to 30 mg COD L-1. The Activated Sludge Model 3 (ASM3), which is a model that takes into account substrate storage mechanisms, fitted well experimental data and allowed confirming that feast and famine cycles in sequential batch reactor favor storage. These results also show that in situ pulse respirometry can be used for fixed-bed reactors characterization.